Variations in the branching pattern of brachial, ulnar and radial arteries - Ashwini Mutalik; Chandrashekhar Hanji; Sanjeev I Kolagi; G B Rairam (Wolters Kluwer Medknow Publications, 2015)
During routine dissection of a cadaver alloted to the undergraduate students in the department of anatomy in SN Medical College, Bagalkot, the authors found multiple variations in the branching pattern of brachial, ulnar and radial arteries. There was high division of brachial artery into ulnar and radial arteries. The profunda brachii originated from brachial artery as usual while superior and inferior ulnar collateral arteries originated from ulnar artery.The radial artery gave origin to common interosseous artery which further divided into anterior and posterior interosseous arteries. All the three arteries i.e. brachial, ulnar and radial were considered as superficial arteries as they were superficial throughout the course. These observations of vascular anomalies are of clinical significance to vascular and plastic surgeons.